Essentials of management: An international perspective / Koontz,Horold: Tata McGraw-hill 8th ed - Weihrich,Heinz
Essentials of management: An international perspective / Koontz,Horold: Tata McGraw-hill 658 K82e8 8th ed No. of Copies : 1